Challenges in oriented strand board R&D in Malaysia / Suffian Misran … [et al.] - Misran, Suffian; Sudin, Rahim; Mohd Yusoff, Mohd Nor; Rusli, Rafeadah (2002)
Oriented strand board (OSB) is a wood based panel product made from wood strands that oriented parallel within others. The strands are bonded together by adhesive with the presence of pressure and heat. The orientation gives high strength properties which nearly resemble to plywood. OSB is widely used in North America and Europe in construction due to its strength and available at big size. However in Malaysia, the utilisation is at the early stage and limited. An early study was made here to develop the product. Several factors effect the product development has been identified and they are raw material, processing of raw material, OSB manufacture. Adhesive utilisation and product utilisation.